Dominant role of excitons in photosynthetic color-tuning and light-harvesting - Timpmann, Kõu; Rätsep, Margus; Freiberg, Arvi (Frontiers in Chemistry, 2023)
Photosynthesis is a vital process that converts sunlight into energy for the Earth’s ecosystems. Color adaptation is crucial for different photosynthetic organisms to thrive in their ecological niches. Although the presence of collective excitons in light-harvesting complexes is well known, the role of delocalized excited states in color tuning and excitation energy transfer remains unclear. This study evaluates the characteristics of photosynthetic excitons in sulfur and non-sulfur purple bacteria using advanced optical spectroscopic techniques at reduced temperatures. The exciton effects in these bacteriochlorophyll a-containing species are generally much stronger than in plant systems that rely on chlorophylls. Their exciton bandwidth varies based on multiple factors such as chromoprotein structure, surroundings of the pigments, carotenoid content, hydrogen bonding, and metal ion inclusion. The study nevertheless establishes a linear relationship between the exciton bandwidth and Qy singlet exciton absorption peak, which in case of LH1 core complexes from different species covers almost 130 nm. These findings provide important insights into bacterial color tuning and light-harvesting, which can inspire sustainable energy strategies and devices.